Endothelial cell transforming growth factor-β receptor activation causes tacrolimus-induced renal arteriolar hyalinosis - Chiasson, Valorie L. (2012)
Arteriolar hyalinosis is a common histological finding in renal transplant recipients treated with the calcineurin inhibitor tacrolimus; however, the pathophysiologic mechanisms remain unknown. In addition to increasing transforming growth factor (TGF)-β levels, tacrolimus inhibits calcineurin by binding to FK506 binding protein 12 (FKBP12). FKBP12 alone also inhibits TGF-β receptor activation. Here we tested whether tacrolimus binding to FKBP12 removes an inhibition of the TGF-β receptor, allowing ligand binding, ultimately leading to receptor activation and arteriolar hyalinosis. We found that specific deletion of FKBP12 from endothelial cells was sufficient to activate endothelial TGF-β receptors and induce renal arteriolar hyalinosis in these knockout mice, similar to that induced by tacrolimus. Tacrolimus-treated and knockout mice exhibited significantly increased levels of aortic TGF-β receptor activation as evidenced by SMAD2/3 phosphorylation, along with increased collagen and fibronectin expression compared to controls. Treatment of isolated mouse aortas with tacrolimus increased TGF-β receptor activation, collagen and fibronectin expression. These effects were independent of calcineurin, absent in endothelial denuded aortic rings, and could be prevented by the small molecule TGF-β receptor inhibitor SB-505124. Thus endothelial cell TGF-β receptor activation is sufficient to cause vascular remodeling and renal arteriolar hyalinosis.